155 Association of smoking with narcotic overdose death following trauma injury admission. (19th September 2017) - Greene, Christina; Smith, Gordon; Mann, David; Longinaker, Nyaradzo
Abstract : Purpose: Due to psychosocial risk factors, injury severity, and post-injury exposure to narcotic analgesics, trauma patients may be at higher risk for narcotic abuse. This study examines overdose risk and modifiable risk factors that could affect mortality of trauma patients due to narcotic overdose. Methods: Trauma injury patients older than 18 years of age who were discharged alive from a Level I Trauma Centre between January 1997 and December 2008 were linked to the National Death Index. Patients who were alive at least 30 days after discharge with no pre-existing alcohol or drug use disorders were included in this study. Chi-squared tests and unadjusted Odds Ratios were used to compare death due to overdose based on the following patient risk factors: demographic, tobacco use, injury mechanism and type, drug urine screen, and blood alcohol level. Cox Proportional Hazard results will be presented forthcoming. Results: This study included a total of 46 504 patients. Thirty-one percent (31%) of patients were smokers at the time of admission and we observed 187 narcotic overdose deaths over the follow-up period. Preliminary results indicated that smoking was significantly associated with mortality due to narcotic overdose (OR 2.13, 95% CI 1.73–3.08). After restricting analyses to patients with no positive drug or alcohol test, we observed an increase in risk of narcotic overdose mortality among smokers (OR 3.92, 95% CI 2.40–6.41). Conclusion: Preliminary results suggest that smoking status is associated with narcotic overdose death, which was higher after the exclusion of patients who tested positive for drugs or alcohol on admission. The association of smoking with narcotic overdose death following trauma admission may be due to differences in injury healing or psychosocial features that predispose smokers to developing addiction. Significance and Contributions: This research informs further narcotic overdose prevention efforts by identifying smoking as risk factor.